From Insecurity to Agency: Professional Competency Development among Non-Formal Early Childhood Educators in Indonesia - Palupi, Retno Endah; Sugito (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2025)
In many non-formal early childhood education (ECE) contexts in Indonesia, especially in rural and community-based institutions, professional competency development remains an underexplored issue despite the prevalence of unqualified teaching staff. This study explores how non-formal early childhood educators without formal educational qualifications develop their professional competencies within the institutional setting of SPS Miftahul Jannah, Sleman, Yogyakarta. Employing a qualitative descriptive case study, data were collected through interviews, participatory observation, and document analysis, then analyzed thematically using Braun and Clarke’s framework. Five core themes emerged: initial professional insecurity as a catalyst for growth, skill transformation through structured training, professional community building via MGMP forums, contextual pedagogical innovations, and the role of mentorship in providing emotional and instructional support. These findings reveal that, despite lacking formal credentials, the educators demonstrated reflective, adaptive, and collaborative professionalism—enabled by sustained institutional support, peer learning, and intrinsic motivation. The study underscores the need to reframe early childhood professionalism to recognize practice-based knowledge and community-embedded expertise. It challenges prevailing assumptions that equate qualification solely with academic degrees and highlights how informal, experiential learning can foster legitimate professional growth. Although this research is limited by its single-site focus and reliance on self-reported data, it offers critical insight into non-traditional pathways of teacher development in under-resourced settings. The findings contribute to the broader discourse on equitable teacher development and call for hybrid certification models that integrate formal education with field-based experiences, thereby institutionalizing inclusive and practice-responsive approaches to professionalization in early childhood education.